Researching social capital for young people’s health - Morgan, Antony; Haglund, Bo J.A. (Socialmedicinsk tidskrift, 2012)
Social capital has the potential to be a resource for societies, contributing to a range of beneficial economic, social and health outcomes. The concept of social capital has emerged as an idea which can help us further articulate the relationship between health and its broader determinants. In the context of young people’s health and wellbeing, the more we invest in social capital as a health asset early on in life, the more young people can experience its positive effects within their families, from their friends, at school and in their local neighborhoods and communities. However, our ability to construct a robust and rigorous evidence base that helps to link and explain the sub domains of social capital to understand how it might be built require a more consistent and systematic approach to research. A range of issues concerning, theory, definition and measurement need to be considered during the planning of such research if the challenges of the concept’s complexity are to be overcome. This paper rehearses 8 of the key issues that have arisen out of past social capital research in order to advance thinking about how it might be best utilized for promoting young people’s health and wellbeing.